Maternal uniparental disomy of chromosome 7: how chromosome 7-encoded imprinted genes contribute to the Silver–Russell phenotype - Matthias Begemann; Anna Lengyel; Eva Pinti; Árpád Ferenc Kovács; György Fekete; Svea Stratmann; Jeremias Krause; Miriam Elbracht; Florian Kraft; Thomas Eggermann (Clinical Epigenetics)
Abstract Background Silver–Russell syndrome (SRS) is a rare congenital growth disorder which is associated with molecular alterations affecting imprinted regions on chromosome 11p15 and maternal uniparental disomy of chromosome 7 (upd(7)mat). In 11p15, imprinted regions contributing to the SRS phenotype could be identified, whereas on chromosome 7 at least two regions in 7q32 and 7p13 are in discussion as SRS candidate regions. We report on DNA and RNA data from upd(7)mat patients and a monozygotic twin pair with a postnatal SRS phenotype carrying a small intragenic deletion within GRB10 to delineate the contribution of upd(7)mat and imprinted genes on this chromosome to the SRS phenotype. Results Genome sequencing in the monozygotic twins revealed a 18 kb deletion within the paternal allele of the GRB10 gene. Expression of GRB10 in blood of the twins as well as in cells from upd(7)mat and upd(7q)mat patients was not altered, whereas RNAseq indicates noticeable changes of the expression of other genes encoded by chromosomes 7 and other genomic regions. Conclusions Our data indicate that intrauterine growth restriction as the prenatal phenotype of upd(7)mat is caused by defective paternal alleles of the 7q32 region, as well as by overexpression of the maternal GRB10 allele whereas a defective GRB10 paternal allele does not cause this feature. The altered expression of MEST in 7q32 by upd(7)mat is associated with the complete SRS phenotype, whereas maternalization or deletion of the paternal GRB10 copy and duplication of the chromosomal region 7p12 are associated with a postnatal SRS-like phenotype.